Praktik Jual Beli Durian Secara Tebasan dalam Kajian Kitab Fatḥu Al-Qarīb (Studi Kasus di Desa Mantenan Giyanti Kecamatan Candimulyo Kabupaten Magelang) - Siti Khaizul Mustaqimah; Ahmad Mustofa; M Pudail (Wahana Islamika: Jurnal Studi Keislaman, 2020)
The purpose of this study is to investigate the practice of buying and selling durian in slashes in the village mantenan Giyanti Candimulyo District of Magelang and to know the views of jurisprudence against such practice in the study of the book of Fatḥu al-Qarīb. This type of research is in the form of descriptive qualitative way through data reduction, data presentation and conclusion, Data was collected by observation, interview, and documentation directly to the people in the village Mantenan Giyanti, namely 5 penebas durian, durian tree 4 owners and other related parties. Results from this study showed that the practice of buying and selling durian in the blow has become a habit people and do when durian has not seen goodness. But there are also penebas who bought durian durian currently been aged about 5 months and nearly ripe. According to the jurisprudence perspective in the study of the book of Fatḥu al-Qarīb an when it has not seen goodness is not valid because it contains gharar legal (vagueness) and could be detrimental to either party. Although buying and selling is prohibited in Islam, but people still carry out this practice on the grounds if the contract slashes replaced by a lease agreement or purchase contract then becomes valid law. However, this in the context of the book Fatḥu al-Qarīb was still judged invalid because the durian tree can not be taken usefulness, but could only take the fruit. Islam which in this case can be called by ḥīlah syar'i law is engineered to change laws that unauthorized origin becomes valid by changing the contract. But can only take the fruit. Islam which in this case can be called by ḥīlah syar'i law is engineered to change laws that unauthorized origin becomes valid by changing the contract. But can only take the fruit. Islam which in this case can be called by ḥīlah syar'i law is engineered to change laws that unauthorized origin becomes valid by changing the contract.